High parasite diversity in a neglected host: larval trematodes of Bithynia tentaculata in Central Europe. (2020) - Schwelm, J.; Kudlai, O.; Smit, N.J.; Selbach, C.; Sures, B.
Abstract: Bithynids snails are a widespread group of molluscs in European freshwater systems. However, not much information is available on trematode communities from molluscs of this family. Here, we investigate the trematode diversity of Bithynia tentaculata, based on molecular and morphological data. A total of 682 snails from the rivers Lippe and Rhine in North Rhine-Westphalia, Germany, and 121 B . tentaculata from Curonian Lagoon, Lithuania were screened for infections with digeneans. In total, B. tentaculata showed a trematode prevalence of 12.9% and 14%, respectively. The phylogenetic analyses based on 55 novel sequences for 36 isolates demonstrated a high diversity of digeneans. Analyses of the molecular and morphological data revealed a species-rich trematode fauna, comprising 20 species, belonging to ten families. Interestingly, the larval trematode community of B. tentaculata shows little overlap with the well-studied trematode fauna of lymnaeids and planorbids, and some of the detected species ( Echinochasmus beleocephalus and E. coaxatus ) constitute first records for B. tentaculata in Central Europe. Our study revealed an abundant, diverse and distinct trematode fauna in B . tentaculata, which highlights the need for further research on this so far understudied host–parasite system. Therefore, we might currently be underestimating the ecological roles of several parasite communities of non-pulmonate snail host families in European fresh waters.